Vegetation Effects on Bacteria and Denitrifier Abundance in the Soils of Two Tidal Freshwater Wetlands in Virginia - Joseph C. Morina; Ember M. Morrissey; Rima B. Franklin (Applied and Environmental Soil Science)
This study examined the abundance of bacteria and nirS-type denitrifiers associated with the rhizospheres of three emergent macrophyte species (Juncus effusus, Typha latifolia, and Peltandra virginica) to gain a greater understanding of plant-microbe interactions in wetland soils. Sampling of plant and soil properties was performed during the growing season (June) and following plant senescence (November) at two tidal freshwater wetlands. Quantitative polymerase chain reaction was used to determine the abundance of bacteria (16S rRNA) and nirS-type denitrifier genes from the rhizosphere and rhizoplane of each plant species and from nearby unvegetated soils. For bacteria, there was a positive rhizosphere effect that did not differ significantly across plant species. In contrast, significant differences in the abundance of nirS-type denitrifiers were observed across the plant species. Rhizosphere abundance was ∼2-fold greater in Peltandra virginica and 4-fold greater in Typha latifolia compared to Juncus effusus. For both bacteria and nirS-type denitrifiers, plant effects were greater during the growing season, and abundance was highly correlated with soil pH, moisture, and organic matter content. Overall, these results demonstrate plant effects on the rhizosphere microbial community can be species‐specific and that there is a synergistic relationship between plant species and environmental conditions.